Membedah Aplikasi SISNU bagi Manajemen Organisasi NU - Agus Salim Chamidi (LPPM Institut Agama Islam Nahdlatul Ulama Kebumen, 2023)
The Nahdlatul Ulama Strategic Information System or SISNU digital application is an innovative product among NU organizations in Central Java. This article aims to take a more in-depth look at what and how SISNU is and at the same time analyze its benefits for the NU organization itself. This research tries to use a content analysis approach to the SISNU application, and then compiles the results using a narrative descriptive model. The conclusion of this research is that SISNU is relatively easy to operate and has strategic benefits for local NU organizations. That innovation in creating digital application regarding organizational information system can facilitate the work of organizational management itself.